Intelligent disturbance rejection for robust tracking performance of X-Y positioning system - Raafat, Safanah M.; Akmeliawati, Rini (2010)
In this paper, design and implementation of an intelligent disturbance weighting function for H-based precision positioning control system is presented for an AC motor drive X-Y table positioning mechanism. The system works with a robust feedback controlled, enhanced by an outer loop integral control. The objective is to achieve high tracking and contouring performances even in the presence of uncertainties and disturbances. The effect of crosstalk between the two axes is considered as disturbance that is treated by intelligent estimated disturbance weighting functions using adaptive neuro fuzzy inference system (ANFIS). The developed controller is implemented experimentally, and a tracking performance of less than 1m is achieved. Contouring error of less than 1m is achieved as well. Index Terms- intelligent H-based precision positioning control system, tracking performances, X-Y table positioning mechanism, AC motor drive, disturbance weighting function.